Catalyst-free ultrasonic-promoted multicomponent synthesis of tertiary α-amino phosphonates. (20th June 2017) - Kalla, Reddi Mohan Naidu; Bae, Jaeyeong; Kim, Il
Abstract : A highly efficient and green protocol has been developed for the synthesis of novel tertiary α-amino phosphonates via a catalyst-free multi-component Kabachnik–Fields reaction under ultrasound irradiation. Abstract : A highly efficient and green protocol has been developed for the synthesis of a new class of tertiary α-amino phosphonates (TAPs) via the Kabachnik–Fields reactions of substituted salicylaldehydes and 2-hydroxy naphthaldehyde, di- n -butylamine, and di-or tri-alkylphosphites in water under ultrasound irradiation as well as under conventional conditions. These multi-component reactions were performed at room temperature without using any catalysts in water. The TAPs were obtained in higher yields (84% to 94%) within shorter reaction times (6 min to 35 min) than those of conventional reactions after simple workup and purification procedures.